Investigating rare genetic variants in common migraine - Weir, G (2014)
Migraine is a highly prevalent headache disorder imposing a significant burden of disability on human health worldwide. The headache is believed to arise from activation of trigeminal pain pathways, with CNS regions also playing an integral role in attack initiation and progression. Recent genetic associations have been made, but there is a need to convert these into relevant experimental models to study underlying disease mechanisms. Herein, I detail functional analysis of two deleterious variants in the genes KCNK18 and SLC12A3, that segregate with migraine with aura in one large pedigree. Gene function has been studied in a range of cell models, from heterologous expression systems and primary neuronal cultures, to Induced Pluripotent Stem (iPS) cell-derived nociceptors. In this context, the protein products of KCNK18 and SLC12A3 have been shown to modulate parameters of neuronal excitability, including baseline membrane properties and firing patterns. Migraine attacks are not wholly attributable to perturbations in peripheral pathways. I have shown that these genes are also expressed within the CNS in a small number of discreet regions, suggesting a possible role in central processing. Utilizing recently defined genetic variants and physiological cell- based models, will provide a platform for mechanistic insights into migraine pathogenesis and allow for the development of drug screening assays for new migraine therapies.